PERAN ORANG TUA DAN GURU DALAM PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS - Lalita, Almira Chandra; Haikal, Deffa Rafli; Aswati, Dewi; Jaya, Indra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education for children with special needs (ABK) requires intensive support from parents and teachers to ensure the child's development and welfare. Parents have an important role in providing love, attention and deep understanding, while teachers have an important role in creating inclusive learning programs. and individualistic. The purpose of writing this scientific article is to find out the role of teachers and parents in the learning of children with special needs (ABK). This research was conducted using qualitative research methods, literature study or literature research. The data taken comes from research that already exists on the internet. The research results show that the role of parents in the education of ABK is very important and multifaceted. They serve as a child's primary advocate, working with schools to plan and implement educational programs that meet their child's unique needs. In addition, parents also provide critical emotional support for their children, helping them overcome obstacles and foster self-confidence. On the teacher's side, this research highlights the importance of in-depth knowledge of a child's special needs and the ability to adapt teaching methods. Teachers are identified as the main agents in implementing an inclusive learning approach and facilitating the social integration of ABK with their peers. The conclusion obtained is that teachers and parents have their respective roles in educating children with special needs, where they have a very important role for education. children with special needs (ABK).